EFFICIENCY OF DIETARY NITROGEN UTILIZATION AND DIGESTIVE METABOLISM OF DAIRY COWS FED DIFFERENT NITROGEN SOURCES AND SUGARCANE - J. R. Naves; E. F. de Jesus; C. M. M. R. Martins; T. Tomazi; J. E. de Freitas Junior; F. P. Rennó; M. V. Santos (Journal of Animal and Plant Sciences, 2015)
The aim of this study was to evaluate four main sources of dietary nitrogen on the efficiency of nitrogen utilization and digestive metabolism of dairy cows fed diets with sugarcane as forage. Twelve multiparous Holstein cows, averaging 150 days in milk and 16.9 kg of milk/day, were distributed into three balanced and contemporary 4 × 4 Latin squares. The study consisted of four experimental periods of 21 days, with 14 days for diet adaptation and the remainder for sampling. Cows were fed isoproteic diets (157.0 g CP/kg DM) and sugarcane as the exclusive forage. The following main nitrogen dietary sources were evaluated: control - soybean meal and urea; soybean meal associated to high level of urea; raw soybean; and, corn gluten meal. Dietary nitrogen sources had no effect on ruminal pH and on microbial protein synthesis. However, the concentrations of ruminal ammonia, urea and blood urea nitrogen were lower for cows fed raw soybean than for cows fed the other nitrogen sources. In conclusion, the utilization of raw soybean as dietary main nitrogen source increases the efficiency of dietary nitrogen utilization of dairy cows fed diets with sugarcane as forage.
Keywords: blood parameters; nitrogen balance; protein synthesis; ruminal fermentation and degradability